The frequency of CCR5 promoter polymorphisms and CCR5 32 mutation in Iranian populations - Mohammad Zare-Bidaki (Iranian Journal of Basic Medical Sciences, 2015)
Evidence showed that chemokines serve as pro-migratory factors for immune cells. CCL3, CCL4 and CCL5, as the main CC  chemokines subfamily members, activate immune cells through binding to CC chemokine receptor 5 or CCR5. Macrophages, NK cells and T lymphocytes express CCR5 and thus, affected CCR5 expression or functions could be associated with altered immune responses. Deletion of 32 base pairs (D 32) in the exon 1 of the CCR5 gene, which is known as CCR5 D 32 mutation causes down regulation and malfunction of the molecule. Furthermore, it has been evidenced that three polymorphisms in the promoter region of CCR5 modulate its expression. Altered CCR5 expression in microbial infection and immune related diseases have been reported by several researchers but the role of CCR5 promoter polymorphisms and CCR5 D 32 mutation in Iranian patients suffering from these diseases are controversial. Due to the fact that Iranian people have different genetic backgrounds compared to other ethnics, hence, CCR5 promoter polymorphisms and CCR5 D 32 mutation association with the diseases may be different in Iranian patients. Therefore, this review addresses the most recent information regarding the prevalence as well as association of the mutation and polymorphisms in Iranian patients with microbial infection and immune related diseases as along with normal population.